2022
DOI: 10.1029/2022jf006640
|View full text |Cite
|
Sign up to set email alerts
|

How Small Slip Surfaces Evolve Into Large Submarine Landslides—Insight From 3D Numerical Modeling

Abstract: Submarine landslides are a major marine geohazard affecting resilience of offshore infrastructure and coastal urban centers. Attention has previously been paid to quantifying post‐failure dynamics of catastrophic submarine debris flows and their consequences. However, pre‐failure initiation and growth of a small slip surface evolving into a large submarine landslide are still less understood. This study aims to explore the physical failure mechanism of submarine landslides initiated from small slip surfaces an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 44 publications
0
13
0
Order By: Relevance
“…The latter author reports a ratio between cross-slope and down/up slope dimensions of the release area to be around 2.1 for unconfined conditions. The shape of our release area also differs from that of Zhang & Puzrin (2022) with a mismatch very likely due to a different slab constitutive model (von Mises versus CCC).…”
Section: Discussionmentioning
confidence: 88%
See 1 more Smart Citation
“…The latter author reports a ratio between cross-slope and down/up slope dimensions of the release area to be around 2.1 for unconfined conditions. The shape of our release area also differs from that of Zhang & Puzrin (2022) with a mismatch very likely due to a different slab constitutive model (von Mises versus CCC).…”
Section: Discussionmentioning
confidence: 88%
“…Gaume & Reuter (2017) and Reuter & Schweizer (2018) later proposed novel methods to describe snow instability by combining limit equilibrium and finite element simulations. More recently Zhang & Puzrin (2022) proposed a depth-averaged finite difference method for the initiation and propagation of submarine landslides. Yet, so far, approaches combining a mechanical release model, variable material properties and complex topography are still scarce.…”
Section: Introductionmentioning
confidence: 99%
“…The depth-integrated method is used to model terrestrial and submarine landslides in cases where the thickness of the sliding body is significantly smaller than its length. [37][38][39][40][41][42] The small thickness to length ratio of such slides allows the stresses and strains of the sliding body to be averaged over its thickness. As a result, the numerical model can be represented by a set of finite bar elements connected via mutual nodes (Figure 3).…”
Section: Formulation Of Sliding Layer Bar Elementsmentioning
confidence: 99%
“…This assumption may have its limitation when considering a margin polygon (e.g., see polygon 1 in Figure 14). In this work, we use the outermost lateral extent of such polygons and construct lines normal to the contour lines to create the associated quasi-stable polygons, 18,19,42 however, have studied the effect of out-of-plane geometry on the critical shear stress ratio for planar and conical slopes. Their studies showed that the shear surface may grow in the transverse direction due to downslope movement of the sediments and that the growth extent is related to the aspect ratio and area size of the pre-softened zone (or failure initiation zones in this case).…”
Section: Limitations Challenges and Further Researchmentioning
confidence: 99%
See 1 more Smart Citation